Shoot on sight is it a crime to be a muslim? - Shah, Naseeruddin 1950-; Puri, Om 1950-2017; Grover, Gulshan 1955- (High Fliers, 2008)
After the July 7, 2005 London bombing, a suspected Muslim is killed by the police. Commander Tariq Ali, a Muslim officer is entrusted to investigate the police shooting. Distrusted by both his superiors in the police, and his fellow Muslism, he finds his inquiry hampered from all sides. When evidence surfaces pointing to the slain man's innocence, as well as the existences of a terrorist cell operating in his own backyard. Tariq must face the realization that sometimes, the right decision is the hardest one to make
Original: UK 2007
Farbe, Bildformat 16x9 anamorphic, DVD5
Keywords: DVD-Video